PENGARUH IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN DI PT. PINDAD PERSERO BANDUNG - Baizani, Ayu Hajari; Sari, Zufita (STIBANKS Al Ma'soem Bandung, 2018)
This study aims to determine the effect of organizational climate on employee performance at PT. PINDAD Persero Bandung. This research is quantitative research. The analysis technique used was Pearson correlation analysis and simple linear regression analysis with 5% significant level. The results of research show that: (1). There is a positive and significant influence between organizational climate on employee performance in PT. PINDAD Persero Bandung. (2) The contribution value of organizational climate influence on employee performance is 32,7% while the rest equal to 67,3% influenced by other factor not observed.